Apatinib combined with S-1 as second-line therapy in advanced gastric cancer. Issue 17 (30th April 2021) - Qiu, Zhi-Yuan; Qin, Rong; Tian, Guang-Yu; Zhang, Zhao; Chen, Meifang; He, Han; Xi, Yan; Wang, Yan
Abstract : Abstract: Advanced gastric cancer (AGC) patients are not tolerant to the toxicities of traditional chemotherapy and its second-line therapeutic regimens are limited. The aim of the present study is to evaluate the efficacy and safety of apatinib combined with S-1 as the second-line therapy for AGC patients. Patients with AGC were enrolled in this study. Patients received oral apatinib (250 mg to 500 mg once daily) and S-1(40 mg/m 2 twice daily) on days 1–14. Each cycle was 28 days and one course of treatment consisted of 2 cycles. Clinical efficacy and adverse events (AEs) were observed. Kaplan–Meier method was used for survival analysis. From November 2015 to December 2017, 58 AGC patients who failed first-line chemotherapy were enrolled and assessed retrospectively. According to the Response Evaluation Criteria in Solid Tumors (RECIST) standard, all patients were evaluable for response. None achieved CR, and 10 (17.2%) achieved PR (95% CI 7.2%–27.3%). SD was observed in 58.6% (34/58) of patients (95% CI 45.6%–71.7%) and NR in 24.1% (14/58) of patients (95% CI 12.8%–35.5%). The objective response rate (ORR) and the disease control rate (DCR) were 17.2% and 75.8% respectively. The median progression-free survival (PFS) and median overall survival (OS) were 143.1 days (95% CI 121.7–164.5) and 211.6 days (95% CI 162.9–219.7) respectively. The multivariate analysis showed that the ECOG PS was the independent factor of PFS and OS for AGC patients (PFS: HR = 3.565, 95% CI: 2.25–5.65, P < .001; OS: HR = 3.676, 95% CI: 2.29–5.89, P < .001). The main AEs were fatigue (72.4%), hypertension (46.6%), and leukopenia (48.3%). Apatinib combined with S-1 showed promising efficiency and was well tolerated as the second-line therapy for AGC patients. ECOG PS was the independent factor of PFS and OS for AGC patients. AEs were moderate and controllable, and leukopenia or hypertension was predictable factors for the PFS and OS of AGC patients.